2016
DOI: 10.1021/acs.biomac.6b00318
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Stiffness Combined with Hepatocyte Growth Factor Modulates Endothelial Cell Behavior

Abstract: Endothelial cells (ECs) play a crucial role in regulating various physiological and pathological processes. The behavior of ECs is modulated by physical (e.g., substrate stiffness) and biochemical cues (e.g., growth factors). However, the synergistic influence of these cues on EC behavior has rarely been investigated. In this study, we constructed poly(l-lysine)/hyaluronan (PLL/HA) multilayer films with different stiffness and exposed ECs to these substrates with and without hepatocyte growth factor (HGF)-supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 65 publications
1
48
0
Order By: Relevance
“…The cell resistance of the PCUL1‐PO samples, regardless of the VEGF surface density [Figure (A)], could be assigned to the low stiffness of the bulk material that possessed the lowest hard segment content (29.6%) among the three PCUL x ‐PO materials ( x = 1, 2, and 3, Table ). Previous studies have demonstrated that soft materials inhibit EC adhesion and proliferation, and grafting with growth factors cannot change the stiffness‐dependent manner of endothelial function . Both PCUL2‐PO and PCUL3‐PO possessed similar hard segment contents (39.7% vs. 38.9%, Table ), but the latter possessed much more PEG content (11.2% vs. 31.1%, Table ).…”
Section: Discussionmentioning
confidence: 95%
“…The cell resistance of the PCUL1‐PO samples, regardless of the VEGF surface density [Figure (A)], could be assigned to the low stiffness of the bulk material that possessed the lowest hard segment content (29.6%) among the three PCUL x ‐PO materials ( x = 1, 2, and 3, Table ). Previous studies have demonstrated that soft materials inhibit EC adhesion and proliferation, and grafting with growth factors cannot change the stiffness‐dependent manner of endothelial function . Both PCUL2‐PO and PCUL3‐PO possessed similar hard segment contents (39.7% vs. 38.9%, Table ), but the latter possessed much more PEG content (11.2% vs. 31.1%, Table ).…”
Section: Discussionmentioning
confidence: 95%
“…examined the migration, proliferation, and adhesion of endothelial cells (ECs) and observed dependence on substrate stiffness. The growth of ECs can be promoted with the presence of hepatocyte growth factor (HGF; Figure ) …”
Section: Multiple Forcesmentioning
confidence: 99%
“…Chang et al showed that hepatocyte GF (HGF) has a stronger effect on endothelial cells on lower stiffness substrates, in terms of cell migration and differentiation. [133] Using LbL-based substrates of different stiffness, they demonstrated that endothelial cell adhesion, migration and proliferation were positively correlated with increasing substrate stiffness and this behaviour was further promoted by HGF. Interestingly, they showed that the effect of HGF on cell migration and proliferation was stronger on soft substrates, suggesting that HGF can profoundly influence the stiffness-dependent endothelial cell response.…”
Section: The Interplay Between Growth Factor Signalling and Mechanotrmentioning
confidence: 99%
“…functionality on stiff substrates in the presence of HGF was still below functionality on softer substrates in the absence of HGF. [133] The interplay between stiffness and growth factor signalling has also been investigated in the context of MSC differentiation, with different results depending on the GF and immobilisation technique used. Zouani et al used surfaces of different stiffness and a BMP-2 mimetic-peptide to identify a minimal threshold of stiffness (≈3.5 kPa) below which the presence of the GF had no effect on MSC differentiation.…”
Section: The Interplay Between Growth Factor Signalling and Mechanotrmentioning
confidence: 99%